Process for massage therapy practice and essential assessment. Issue 3 (July 2016) - Kennedy, Ann Blair; Cambron, Jerrilyn A.; Sharpe, Patricia A.; Travillian, Ravensara S.; Saunders, Ruth P.
Summary: Background: Little evidence exists about processes in massage therapy practice. Investigating current frameworks is warranted. This qualitative study is a secondary data analysis using grounded theory to understand how massage therapy experts describe massage therapy practice. Methods: 31 massage therapy experts were invited to a 2-day symposium to discuss best practices for the profession. Through qualitative analysis, memoing, and discussion, the data were summarized into themes. Results: Three themes were identified around massage therapy practice: 1) client centered, 2) structure for practice, and 3) influencing factors. Each theme is clarified and expanded. Discussion: Conceptual models were developed for research and clinical practice and a definition for massage therapy practice was identified. Challenges and limitations are discussed. Conclusion: The goal of providing these models is to give massage therapists tools to deliver the best possible care. The models need testing to see if they help advance the profession.